Giant prolactinomas: the therapeutic approach. (11th June 2013) - Moraes, Aline B.; Marques dos Santos Silva, Cintia; Vieira Neto, Leonardo; Gadelha, Mônica R.
Abstract: Background: Giant prolactinomas are an unusual subset of macroprolactinomas and are more commonly found in men. The goal of this review is to propose a giant prolactinoma definition and discuss the available therapeutic options for biochemical and tumour volume control. Methods: A comprehensive search of all published studies was performed between April and November 2012 in electronic databases (PubMed and Ovid). Results: A giant prolactinoma should be defined as an adenoma with a maximum diameter of more than 4 cm that is associated with serum prolactin above 5300 mIU/l. Regarding treatment, cabergoline is the preferred dopamine agonist for medical management of giant prolactinomas because of its excellent efficacy and tolerability. Normalization of prolactin level and significant tumour reduction may be achieved in the majority of patients. Combined therapy, particularly cabergoline and surgery, may be necessary due to the large tumour load. Radiotherapy and temozolomide may be used for patients with aggressive giant prolactinomas in whom tumour volume control is not achieved with cabergoline and surgery. Conclusion: There is a scarcity of large studies about the management of giant prolactinoma. Cabergoline is the first‐line treatment. However, caution should be exercised when comparing efficacy rates among the different treatment modalities due to the variability in study design and data quality. In this scenario, a 'standard' definition for giant prolactinomas and larger series may be helpful to assess the real efficacy and safety of each therapeutic modality.